Professionalism and Ethics of Accounting in Financial Reporting: An Overview of Nigerian Scenerio - Bushi Kasimu Musa (European Scientific Journal, ESJ, 2019)
This paper focuses on evaluating the concept of professionalism and ethics of accounting standards on the quality of financial reports in Nigeria. To achieve this objective, data was collected from primary and secondary sources. Questionnaires were distributed with the use of simple random sampling technique in selecting a sample size of 75, consisting of accountant and auditors and relevant data obtained. Accounting ethics was measured with professional independence and professional competence, while financial reporting quality was measured using the qualitative attribute of dependability and understandability. Ordinary Least Square was utilised to develop a theoretical equation model to test the formulated hypotheses. Understandability was significant at 5% level in associating with both competence and independence respectively. Reliability was found to be significant at 5% level, only with independence. On the basis of these findings, therefore, it was recommended that corporate bodies should establish ethics compliance department to enhance the enforcement of ethical compliance in the various economy institutions.